EFL LECTURER INTERPERSONAL COMMUNICATION SKILLS IN PRIVATE UNIVERSITY CLASSROOM CONTEXT IN INDONESIA (International Conference on Social and Islamic Studies, 2021)
The aim of this paper was to analyze the interpersonal communication skills of EFL lecturers in the context of a private university classroom. This research employed the qualitative research. data were analyzed descriptively through a three-stage model, namely data display, data reduction and Conclusions: Drawing/verification. The data resources for the research chosen through purposive sampling were three lecturers taught at in Universitas Muslim Indonesia. The results of the research found here were five interpersonal communication skills used by lecturers when teaching, namely: openness, supportive attitude, positivity, equality, and empathy.